THE EMERGENCE OF AGENCIES: A NEW STRUCTURAL PARADIGM IN PUBLIC ADMINISTRATION? (Journal of Teleological Science, 2024)
The adoption of New Public Management (NPM) has brought with it changing values, changing organizational structures, redefining roles and introducing new actors, as well as a new management culture (Ferlie et.al, 1996). One of the main structural changes introduced in the last decades is the introduction of agencies (Pollitt et.al, 2001). It is in this context that the relevance of this essay arises, highlighting the main consequences associated with these changes. To reach viable conclusions the way the data will be treated will help a lot. Through literature review it will be possible to study the theme from its beginnings to more recent studies, equally important in that they will help to better understand the progression of the studies.
Keywords: New Public Management; Public Administration; Change of Organizational Structure